Proteinuria is risk factor for abdominal aortic aneurysm: a nationwide population-based study - Kang Woong Jun; Ju-hwan Yoo; Jin-Hyung Jung; Kyung-jai Ko; Hyung-jin Cho; Mi-hyeong Kim; Kyung-do Han; Jeong-kye Hwang (BMC Public Health)
Abstract Background Proteinuria is a well-known risk factor for cardiovascular disease. However, the impact of proteinuria on abdominal aortic aneurysm (AAA) remains unclear. In this study, we aimed to investigate the association between proteinuria and AAA. To assess the correlation between proteinuria measured by the urine dipstick test (UDT) and the risk of AAA by using nationwide population cohort data. Methods This retrospective cohort study used data from the Korean National Health Insurance database for individuals who had health check-ups in 2009. Incident AAA was ascertained through the end of 2019. The study population was classified into the following five groups based on the UDT result: negative; trace; 1+; 2+; and ≥ 3+. The primary endpoint was newly developed AAA during the study period. Results A total of 9,938,329 patients were enrolled. During a median follow-up of 9.3 years (interquartile range 9.1–9.6), 20,760 (0.2%) AAA events were identified, and the incidence rates of AAA were 2.21, 2.55, 4.20, 5.77 and 7.49 per 10,000 per year in the negative, trace, 1+, 2 + and 3 + ≤ proteinuria groups, respectively, compared with those without proteinuria (P <.001). There was a positive correlation between the degree of proteinuria and the risk of AAA, which was consistent regardless of all estimated glomerular filtration rate categories. Conclusion Proteinuria as measured by the UDT was strongly associated with AAA and acted as an independent risk factor. These findings suggest that proteinuria may serve as a potential marker for identifying individuals at higher risk of AAA.